2013
DOI: 10.1037/h0093990
|View full text |Cite
|
Sign up to set email alerts
|

Do individual characteristics explain variation in sanction risk updating among serious juvenile offenders? Advancing the logic of differential deterrence.

Abstract: Recent theoretical and empirical research in deterrence has detected evidence of differential deterrability, or that the effect of sanctions is not uniform across persons. Important questions in this area remain to be explored, and this study considered a central question: Whether important across-individual variability in risk perceptions can be tied to important individual-level factors. This article extends the Bayesian risk updating model developed by Anwar and Loughran (2011) to determine whether the weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 70 publications
2
55
1
1
Order By: Relevance
“…Neither the literature on situational crime prevention nor Bayesian learning theory is well suited for explaining how individuals’ dispositions or personalities influence their sanction perceptions. Nevertheless, the results of studies have shown that several personality traits are strongly associated with perceived punishment risk (Pickett and Bushway, ; van Gelder and de Vries, , ) and influence sanction perception updating (Thomas, Loughran, and Piquero, ). In a seminal study, van Gelder and de Vries () found that honesty‐humility, agreeableness, extraversion, conscientiousness, and self‐control were all associated with perceived sanction risk.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neither the literature on situational crime prevention nor Bayesian learning theory is well suited for explaining how individuals’ dispositions or personalities influence their sanction perceptions. Nevertheless, the results of studies have shown that several personality traits are strongly associated with perceived punishment risk (Pickett and Bushway, ; van Gelder and de Vries, , ) and influence sanction perception updating (Thomas, Loughran, and Piquero, ). In a seminal study, van Gelder and de Vries () found that honesty‐humility, agreeableness, extraversion, conscientiousness, and self‐control were all associated with perceived sanction risk.…”
Section: Resultsmentioning
confidence: 99%
“…Such decisions often occur when actors are intoxicated and/or viscerally aroused (Loewenstein, Nagin, and Paternoster, ; Pridemore, ), with incomplete information, and under conditions of chaos and/or time‐sensitivity. Moreover, there is wide heterogeneity in the capacity and inclination for abstract and otherwise effortful thinking (Pickett and Bushway, ; Thomas, Loughran, and Piquero, ). For example, individuals with low cognitive reflection are less likely to persevere past an impulsive but incorrect conclusion to obtain the correct one with added cognitive effort (Frederick, ).…”
Section: Heuristics and The Perception Of Sanction Riskmentioning
confidence: 99%
“…Second, individual differences in dual‐system processing might moderate the association between socialization by peers and decision outcomes. Individuals who tend to rely on the fast system may overweigh information from the current situation at the expense of their experiences in the past, thereby making prior socialization less relevant (Piquero & Pogarsky, ; Thomas & McGloin, ; Wikström, , see also Thomas, Loughran, & Piquero, on verbal IQ). It is also possible that those individuals find it difficult to translate vicarious observations to their own situation, which would imply that socialization has less impact on their developing perceptions.…”
Section: Combining Insights On Socialization Situational Peer Influementioning
confidence: 99%
“…One example is a formal, rational model of dynamic Bayesian updating of perceptions of detection risk proposed and tested by Anwar and Loughran (). Systematic departures from this standard model have been subsequently studied by Thomas, Loughran, and Piquero () and by Pogarsky et al. ().…”
Section: State Of Criminological Rational Choice Theorymentioning
confidence: 94%